Teaching Speaking Skills Using the Spinning Wheel Game in Senior High School - Razan; Maria Ulfa, Siti (Penerbit STKIP PGRI Bangkalan, 2025)
Students in Senior High School still have some difficulty in speaking English language fluently. The researcher of this study research the student’s speaking skill by using the Spinning Wheel Game media. In this study, the researcher used qualitative method with case study design. The researcher focuses on the student’s fluency in speaking English language. The primary data of this study is from the observation and the result of interview, meanwhile the secondary data is from books, journal, personal document, and official written documents. The instrument of this study are field note observation, interview guide, and documentation. The purpose of this study is to know the use of the Spinning Wheel Game in teaching speaking skill and the student’s response in using Spinning Wheel Game. The result of this study showed that Spinning Wheel Game helps students in the class. the students were active, enthusiastic, focused to the material and comprehend the material well. The Spinning Wheel Game media also helps students in speak English language in terms of their fluency and their confidence.